Conceptual history in the European space - Steinmetz, Willibald; Freeden, Michael; Fernández Sebastián, Javier, 1952- (European Conceptual History Ser., 2017)
The result of extensive collaboration among leading scholars from across Europe, Conceptual History in the European Space represents a landmark intervention in the historiography of concepts. It brings together ambitious thematic studies that combine the pioneering methods of historian Reinhart Koselleck with contemporary insights and debates, each one illuminating a key feature of the European conceptual landscape. With clarifying overviews of such contested theoretical terrain as translatability, spatiality, and center-periphery dynamics, it also provides indispensable contextualization for an era of widespread disenchantment with and misunderstanding of the European project.